Coupled autotransformer and magnetic-control soft-start method for super-large-capacity high-voltage motors - Jiaxin Yuan; Chuansheng Wang; Shan Yin; Liangliang Wei; Kazuhiro Muramatsu; Baichao Chen (High Voltage, 2019)
The large current generated by a direct start of the super-large-capacity high-voltage induction motor would have a huge impact on the power grid as well as the motor itself. Traditional soft starters have the shortcomings of discontinuous adjustment, voltage sags, sudden torque mutation, secondary current impact and high cost. To resolve this issue, the authors propose a novel coupled autotransformer and magnetic-control (CATMC) soft-start method. The structure of the new CATMC soft starter combines the functions of the autotransformer and magnetic control reactor via an innovative electric and magnetic circuit design. In this study, the authors analyse the magnetic circuit structure and working principles of the CATMC soft starter. Then, to validate its principle and performance, the authors conduct a simulation study using ANSYS software and design and test an 18 MW/10 kV CATMC soft starter prototype. The simulation results demonstrate that the CATMC soft starter effectively avoids secondary current impact and constrains the motor starting current to <2.5 times the rated current. The public connection point bus voltage also meets the voltage sag requirement of the IEEE standard and reduces the impact on the power grid.